Annotated checklist of Hygrophoraceae (Agaricales, Basidiomycota) in Ukraine - Chvikov, V; Prylutskyi, O (ХНПУ імені Григорія Сковороди, 2021)
Hygrophoraceae is a family within Agaricales, which comprises 26 genera and approximately 690 agaricoid species, including ectomycorrhizal, lichen-forming, bryophilous, humus and litter decomposing fungi. Some of these species especially those from genera Cuphophyllus, Hygrocybe, Neohygrocybe and Porpolomopsis are associated with natural grasslands and show extreme sensitivity to the presence of nitrogen-containing fertilizers in their substrate. This makes them indicative species of grasslands of high conservation value. While casual observations of Hygrophoraceae of Ukraine were incorporated in studies of agaricoid fungi as a whole, this family has never been in the focus of special research. Previously accumulated data on the diversity of Hygrophoraceae in Ukraine must be aggregated and revised. We have summarized all available data on the occurrences of Hygrophoraceae in Ukraine, including published papers, open databases, citizen science observations, and the previously unpublished original collection materials. Also, we provide an original description of the rare European species Haasiella venustissima (Fr.) Kotl. & Pouzar ex Chiaffi & Surault, which is reported for the first time from the territory of Ukraine. The resulting checklist of Hygrophoraceae of Ukraine includes 66 species. Leading genera are Hygrophorus (22 species), Hygrocybe (17) and Arrhenia (10); 5 species among them (Hygrocybe punicea, Hyrgocybe splendidissima, Neohygrocybe nitrata, Neohygrocybe ovina, Porpolomopsis calyptriformis) are threatened and according to “IUCN Red List” considered “Vulnerable”. The finds of 22 species in Ukraine were reported as doubtful. Carpathian Forests and LeftBank Forest-Steppe are the phytogeographic regions with the highest known diversity of Hygrophoraceae; however, this may be explained by the sampling bias. In spite of the long history of investigations and rather big amount of data, the checklist may be significantly updated by further surveys of grassland habitats, wider using of molecular identification methods, and by implementation of the best practices in biodiversity data management, e.g. photographing of fresh fruit bodies, digitization and databasing of observations.
Анотований чекліст Hygrophoraceae (Agaricales, Basidiomycota) в Україні
Keywords: agarics; literature review; citizen science; Haasiella venustissima; first record; Ukraine